Development of a Cloud-Point Extraction Method for Cobalt Determination in Natural Water Samples - Mohammad Reza Jamali; Mohammad Gholinezhad; Saiedeh Balarostaghi; Reyhaneh Rahnama; Seyed Hojjat Allah Rahimi (Journal of Chemistry)
A new, simple, and versatile cloud-point extraction (CPE) methodology has been developed for the separation and preconcentration of cobalt. The cobalt ions in the initial aqueous solution were complexed with 4-Benzylpiperidinedithiocarbamate, and Triton X-114 was added as surfactant. Dilution of the surfactant-rich phase with acidified ethanol was performed after phase separation, and the cobalt content was measured by flame atomic absorption spectrometry. The main factors affecting CPE procedure, such as pH, concentration of ligand, amount of Triton X-114, equilibrium temperature, and incubation time were investigated and optimized. Under the optimal conditions, the limit of detection (LOD) for cobalt was 0.5 μg L-1, with sensitivity enhancement factor (EF) of 67. Calibration curve was linear in the range of 2–150 μg L-1, and relative standard deviation was 3.2% (c=100 μg L-1; n=10). The proposed method was applied to the determination of trace cobalt in real water samples with satisfactory analytical results.